2018
DOI: 10.3847/1538-4357/aab88a
|View full text |Cite
|
Sign up to set email alerts
|

Stellar Population Properties of Ultracompact Dwarfs in M87: A Mass–Metallicity Correlation Connecting Low-metallicity Globular Clusters and Compact Ellipticals

Abstract: We derive stellar population parameters for a representative sample of ultracompact dwarfs (UCDs) and a large sample of massive globular clusters (GCs) with stellar masses 10 6 M ⊙ in the central galaxy M87 of the Virgo galaxy cluster, based on model fitting to the Lick-index measurements from both the literature and new observations. After necessary spectral stacking of the relatively faint objects in our initial sample of 40 UCDs and 118 GCs, we obtain 30 sets of Lick-index measurements for UCDs and 80 for G… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 70 publications
2
30
0
Order By: Relevance
“…8 we show [α/Fe] versus total metallicity. The M87 UCDs and GCs, from our work and from Zhang et al (2018), tend to have super-solar alpha ratios indicative of rapid star formation. These ratios also cover a similar range to those of Virgo dE nuclei (although the dE nuclei have a lower mean value).…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…8 we show [α/Fe] versus total metallicity. The M87 UCDs and GCs, from our work and from Zhang et al (2018), tend to have super-solar alpha ratios indicative of rapid star formation. These ratios also cover a similar range to those of Virgo dE nuclei (although the dE nuclei have a lower mean value).…”
Section: Discussionmentioning
confidence: 52%
“…The alpha-element metallicity relation for a range of objects. The plot shows Virgo dE nuclei, UCDs and GCs (Zhang et al 2018) and Coma cluster ultra diffuse galaxies (Ferré-Mateu et al 2018), along with the 3 UCDs and 3 GCs from this study. The well studied M87 UCD S999 from Janz et al (2015) is also shown.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations